WOMEN DEFENCE SYSTEM FOR DETECTING INTERPERSONAL CRIMES - A.Rhagini, Dr.S.Thilagamani (International Journal of Advanced Science and Technology, 2020)
The security for women nowadays is going too worsen in the world. Women are feeling less secure while moving out of the home. To achieve a good position in their life they are facing difficult situations in their life in terms of security. To help the women in times of need there are several security systems available and still they need to be improved for providing security to women. The researchers are concentrating on providing smart security for women. Our model provides about safe and secure system for women which comprises of   location tracking, alert message and evidence collection in terms of live video update.  GPS and GSM are used. When the women is in threat, this GPS module tracks the location of the victim  and by using GSM module the location is sent as alert message  and video of the victim is transferred to the registered contact number. A web camera is placed to capture videos and shared to the registered contact number as evidence.